Augmenting of primary and secondary macronutrients by chopped leucaena leaves used as organic matter in composted sweet potato mounds under tropical humid lowland conditions - M. Peter, Topas; Y. Chung, Ruben; S. Michael, Patrick (International Journal of Environment, 2024)
The importance of chopped leucaena leaves as an organic matter amendment in mounds used for sweet potato production was investigated. Fresh leaves were collected, sun-dried, chopped, and applied to land that was plowed, and mounded with four treatments. The first treatment was set as the control, 1 kg of chopped leaves was applied but not planted in the second, no chopped leaves were applied and planted in the third, and chopped leaves were applied and planted with sweet potato in the fourth treatment, respectively. These were replicated four times and set up for six months in the field. A 500 g of soil samples were taken from the top 0 – 60 cm of the mounds, processed, and analyzed for macronutrients, electrical conductivity, and pH using standard analytical procedures. The results showed that adding the chops increased the content of all the macronutrients. In almost all cases, the application of the chopped leaves and concurrent planting sustained the availability of the nutrients compared to the depletion that occurred when no amendment was made nor planted. The changes in electrical conductivity and pH were within acceptable ranges. These findings have implications for soil fertility management in the humid tropics.